Formulasi and Evaluasi Stabilitas Fisik Suspensi Ubi Cilembu (Ipomea batatas L.) dengan Suspending Agent CMC Na dan PGS Sebagai Antihiperkolesterol - Fitriani, Yeyen Nor; INHS, Cikra; Yuliati, Ninis; Aryantini, Dyah (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2015)
Drug which has small solubility in water is one of the problems that cause instability of pharmaceutical preparations. One drug practically insoluble in water is cilembu (Ipomoea batatas L.). So cilembu (Ipomoea batatas L.) made in form of suspension in order to produce stable preparations in liquid form. Making of the suspension cannot be separated from the suspending agent. CMC Na (Carboxymethylcellulose Sodium) and PGS (pulvis gummosus) is suspending agent which have been studied to produce a stable suspension. Accordingly, this study was conducted to know the suspension evaluation stability cilembu (Ipomoea batatas L.) with a suspending agent CMC Na and PGS as antihypercholesterol. Method of manufacture is dispersion method. Evaluation of physical stability test was conducted on the organoleptic, homogeneity, pH, density, viscosity, sedimentation volume, and redispersion. Data were analyzed with repeated measures and shelflife. Evaluation of physical stability the suspension cilembu with a suspending agent CMC Na and PGS on observations organoleptic, homogeneity, density and redispersion showed no difference, while the pH, viscosity and sedimentation volume were not significant differences (p< 0.05) during 30 days of storage.